Joint Chapter Meeting in Montreal: NYSO / NEMLA / SQACBM - Cohen, Marci (CAML Review / Revue de l’ACBM, 2018)
This report summarizes the November 2018 two-day joint chapter meeting, held in Montreal at McGill University, which involved the New York State-Ontario (NYSO) and New England (NEMLA) chapters of the Music Library Association (MLA) and the Quebec Chapter (SQACBM) of the Canadian Association of Music Libraries, Archives and Documentation Centres (CAML).